(untitled) (Research, Society and Development, 2023)
Peanut has been used as an alternative in crop rotation in large areas of sugarcane. Plants may be subject to residual herbicides in these commercial areas as 2,4D and Picloram are applied for weed control. The objective of this research was to know the initial development of peanut seedlings grown in soil with herbicide residue. The experiment was carried out in August 2022, at Faculdades Integradas Stella Maris (FISMA), located in the Municipality of Andradina, State of São Paulo. The design was completely randomized (DIC), with five doses of the commercial product Dontor® (Picloram Acid and 2,4D Acid) as follows: absence; 1.0; 2.0; 4.0 and 8.0 L ha-1 and with four replications, totaling 20 plots or pots. The maximum point in the peanut response was at the dose of 5.0 liters per hectare of the herbicide 2,4D + Picloram. A dose greater than 5.00 liters per hectare of the herbicide 2,4D + Picloram compromises the development of peanuts. Leaf area and stomatal density responded in a negative linear fashion to herbicide doses.